Spectral-spatial neural network classification of hyperspectral vegetation images. Issue 1 (1st February 2023) - Podlipnov, V V; Firsov, N A; Ivliev, N A; Mashkov, S V; Ishkin, P A; Skidanov, R V; Nikonorov, A V
Abstract: The paper presents the results of a study of the method of classification of vegetation types based on hyperspectral survey data. A hyperspectrometer based on the Offner scheme was used as a shooting equipment. The spatial-spectral architecture of a convolutional neural network is used as a classifier. The experiments performed show the effectiveness of the proposed approach for the classification of vegetation types.